2019
DOI: 10.1111/joms.12527
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of the Influence of March and Simon’s Organizations: The Realized Contribution and Unfulfilled Promise of a Masterpiece

Abstract: March and Simon’s Organizations is a seminal work in management studies. We assess the contribution Organizations has made to management studies through a citation context analysis of 1,400 articles from top management journals. By categorizing the content from Organizations cited in subsequent works, we find that two related categories associated with cognitive limits and routines or programs account for half (50.5%) of all citation contexts since 1990. We also investigate whether citations to Organizations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 150 publications
(178 reference statements)
0
49
0
1
Order By: Relevance
“…We coded the substantively citing articles with a framework that was created along two dimensions: the content and the use of the HR architecture model (c.f., Anderson, 2006;Anderson & Lemken, 2019;Wry et al, 2013). That is, first, we coded which major idea(s) of the HR architecture model, as reviewed in Section 2, was/were used in the article.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We coded the substantively citing articles with a framework that was created along two dimensions: the content and the use of the HR architecture model (c.f., Anderson, 2006;Anderson & Lemken, 2019;Wry et al, 2013). That is, first, we coded which major idea(s) of the HR architecture model, as reviewed in Section 2, was/were used in the article.…”
Section: Methodsmentioning
confidence: 99%
“…Such a classification of the literature has often been adopted, sometimes implicitly, in other literature reviews (e.g. Anderson & Lemken, 2019;Colquitt & Zapata-Phelan, 2007;Wright et al, 2001). For instance, Wright and McMahan (1992) provided a comprehensive review on how theories such as the resource-based view had been applied to SHRM, and emphasized the need for 'rigorous empirical tests' (p. 315), and 'further development and explication' (p. 316) of these theoretical models.…”
Section: Methodsmentioning
confidence: 99%
“…Several citation context analyses have examined whether the content being cited in a focal work has changed over time (e.g., Anderson, 2006;Anderson & Lemken, 2019;Chang, 2013a;McCain & Salvucci, 2006;Richardson & Pysek, 2008), with the implication that the realized contribution of the work can change. Both Cozzens (1985) and Hargens (2000) found that earlier citations to a work were more likely to discuss methods and findings explicitly while later citations made more cursory mentions of knowledge claims or noted how works initiated new fields.…”
Section: Question 3: How Has the Content Cited From The Work Changedmentioning
confidence: 99%
“…One final consideration is whether there is any reason to exclude particular works. For example, researchers may deem it advisable to exclude works that contain an excessive number of citation contexts, such as our (Anderson & Lemken, 2019) decision to exclude Kilduff's (1993) extensive deconstruction of March and Simon's (1958) classic book Organizations. Such sources may be better to discuss individually in a literature review as their sheer number of contexts will make them outliers that bias the results of a numerical analysis of citations.…”
Section: Step 3: Gather the Citation Contexts And Create A Citation Cmentioning
confidence: 99%
“…Next, Anderson and Lemken demonstrate empirically the impact of Organizations on subsequent research (Anderson and Lemken, 2019). They present a citation context analysis of 1,400 articles in eight major management journals.…”
Section: Presentation Of Papersmentioning
confidence: 99%